Preparation and Characterization of Prism-Like ZnO with Pore Structure - Hu, H.M.; Deng, C.H.; Fang, Q.; Zhang, K.H.; Sun, M.; Xuan, H. (Asian Journal of Chemistry, 2012)
Porous zinc oxide microprisms constructed by connected nanoparticles have been successfully prepared by thermal decomposition of the Zn-N2H4 complexes precursor at 600 ºC for 1 h in air, which was synthesized in advance using Zn(CH3COO)2·2H2O as zinc source and hydrazine hydrate as complexing agent through a room-temperature coordination-precipitation technique. The morphology of ZnO inherit that of the precursor. The products were characterized by X-ray diffraction, energy dispersive X-ray spectrometry, field-emission scanning electron microscopy, UV-visible absorption spectrum and photoluminescence spectrum.